PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN TIPE ROLE PLAYING TERHADAP MINAT DAN HASIL BELAJAR IPA PADA MATERI MAKHLUK HIDUP DAN LINGKUNGAN KELAS IV SD INPRES DEKAI KABUPATEN YAHUKIMO - Ardi, Adriana (Magister Pendidikan IPA, UNCEN, 2016)
This research aims to understand the influence of learning IPA by using the role playing method against toward student learning interest and outcomes of the Fourth grade students of SD Inpres Dekai, academic year 2014 / 2015. This research used design double paradigm , with a population of students grade fourth A as a class trial and grade fourth B as class sample research .The collection of data was collected through a test of role playing method, learning interest and the test results previously been tested validation beforehand. The technique of data analysis used SPSS version 16. The conclusion of this research are: ( 1 ) there are influence of the application of a role playing method towards student learning results as much as 0,929; ( 2 ) there are influence of the application of a role playing method against student learning interest of 0,926; ( 3 ) there are relation of the application of a role playing method of student learning results of as much as 92,9 %; ( 4 ) there are relation of the application of a role playing method against interest as much as 92,6%. Keywords :Role Playing Metohd, Studentsâ Interest, Learning Outcomes, Living Beings and The Environment